A 1-year per-patient cost of therapy administration analysis of mosunetuzumab and tisagenlecleucel in relapsed or refractory follicular lymphoma patients receiving two or more lines of systemic therapy - Marco Bellone; Alice Sabinot; Alessandro D’Arpino; Emanuela Omodeo Salè; Daniela Ghislieri; Lorenzo Pradelli (Global & Regional Health Technology Assessment)
Objective: A per-patient cost of therapy administration model was developed to estimate the cost of mosunetuzumab vs. tisagenlecleucel in patients with relapsing or refractory follicular lymphoma (R/R FL) receiving two or more lines of systemic therapy (3L+) from both the Italian hospital and societal perspectives.